Walking on the Edge of the Abyss Conversations with Gustavo Esteva - Lau, Kin Chi.; Escobedo, Rafael; Barkin, David (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
The book is a collection of essays written by Gustavo Esteva over the last 20 years. In this book, Gustavo Esteva, renowned in Mexico as a philosopher on education and on developmentalism, collects four major areas of his writings: on learning, development, autonomy, and interculturality. A memorial to a great thinker, this book stimulates thoughts on developmentalism across the global south. Kin Chi Lau is Adjunct Associate Professor in cultural studies, and also coordinator of the Programme on Cultures of Sustainability, Centre for Cultural Research and Development, Lingnan University. She is also a Founding Member of Global University for Sustainability. Rafael Escobedo does research at the intersection of organizational theory, agrarian, and non-state societies, with a special interest in the role of peasant farmers and seasonal farmworkers subaltern politics. David Barkin is a distinguished professor in Economics, Metropolitan Autonomous University of Mexico, and a founding member of the Ecodevelopment Centre.
1. Introduction -- 2. Learning -- 3. Development -- 4. Autonomy -- 5. Interculturality.
Keywords: Philosophy; Philosophy